Soil amendments influence Pratylenchus penetrans populations, beneficial rhizosphere microorganisms, and growth of newly planted sweet cherry - Watson, Tristan T.; Nelson, Louise M.; Neilsen, Denise; Neilsen, Gerry H.; Forge, Tom A. (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2017)
Replant disease (RD) presents a significant barrier to establishing productive orchards on old orchard soil. Using a field and greenhouse experiment, this study evaluated the influence of agricultural waste compost (AWC) soil amendments, and bark chip mulch (BM) on Pratylenchus penetrans populations and new growth of sweet cherry planted into soil previously used for apple production. Impacts of the treatments on the abundance of rhizosphere microorganisms associated with soil suppressiveness were also evaluated. In the field experiment, fumigation, and preplant incorporation of AWC combined with surface application of BM increased trunk cross-sectional area (TCSA) compared to untreated control plots. Fumigation initially decreased P. penetrans populations in soil, however populations recovered by the end of the first growing season. AWC and BM suppressed P. penetrans populations in roots relative to fumigation or the control. AWC increased the abundance of total bacteria, 2,4-diacetylphloroglucinol-producing (DAPG) bacteria, and pyrrolnitrin-producing (PRN) bacteria in the rhizosphere, relative to fumigation and the control. In the greenhouse experiment, fumigation, AWC, and yard trimmings compost (YTC) increased shoot length of apple and sweet cherry seedlings as well as suppressed P. penetrans populations compared to the control. AWC also increased the abundance of total bacteria, Pseudomonas spp., DAPG+bacteria, and PRN+bacteria relative to fumigation and the control. Overall, composts and BM show potential as alternatives to fumigation for suppression of RD on sweet cherry, with promotion of beneficial rhizosphere microorganisms a possible contributing mechanism in compost-induced soil suppressiveness.